Particle number concentration near road traffic in Amsterdam (the Netherlands): Comparison of standard and real-world emission factors. (May 2016) - Keuken, M.P.; Moerman, M.; Voogt, M.; Zandveld, P.; Verhagen, H.; Stelwagen, U.; Jonge de, D.
Abstract: In this study, NOx and particle number concentration (PNC) at an urban background and a traffic location were measured in the city of Amsterdam (the Netherlands). Modelled and measured contributions to NOx and PNC at the traffic location were used to derive real-world PN emission factors for average urban road traffic. The results for NOx were applied to validate our approach. The real-world PN emission factors (#.km −1 ) were 2.9E+14 (urban road) and 3E+14 (motorway). These values were at least a factor eight higher than dynamometer-based PN emission factors from COPERT 4 and HBEFA databases. The real-world PN emission factors were used to model the contribution to PNC near road traffic in 2014. This was two to three times higher than the PNC urban background along urban roads over 20, 000 vehicles per day and near motorways. The discrepancy between dynamometer-based and real-world emission factors demonstrates the need for more PNC observations to assess actual PN emissions from road traffic. Highlights: Real world PN emission factor for traffic eight times standard emission factor. Real world PN emission factors: 2.9E+14 (urban) and 3E+14 (motorway) #.km −1 . PNC near urban roads three times higher than urban background.